Citizens’ Perceptions on Social Responsibility in Public Administration Organizations: A Case Study on Spain - José Luis VÁZQUEZ; Carlota L. AZA; Ana LANERO (Transylvanian Review of Administrative Sciences, 2016)
This paper analyzes citizens’ expectations on social responsibility of public administration organizations in comparison to other public and private organizations, and argues that the mission attributed to different institutions in society might guide citizens’ perceptions and thresholds of satisfaction with sustainability standards. Three different survey studies were carried out to analyze citizens’ expectations of social responsibility of public administration organizations, private companies and a public university in the same Spanish region. A list of indicators defining internal and external social responsibility practices was developed to compare expectations in the three institutional contexts, and MANOVA was used to test differences between participants in the three surveys. Results support the notion that citizens’ expectations of social responsibility are related to perceived organizational goals in private and public contexts and the specific dimension of responsibility considered. Particularly, participants displayed higher expectations of external social responsibility in public administration organizations than in private companies and the public university analyzed, whereas citizens’ expectations of internal social responsibility were more homogeneous in public and private contexts. Implications of the study and suggestions for further research are discussed.